2017
DOI: 10.1080/17518253.2017.1363297
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis, characterization and antibacterial activity of silver nanoparticles from root extract of Lepidium draba weed

Abstract: View related articles View Crossmark data Citing articles: 17 View citing articles Green synthesis, characterization and antibacterial activity of silver nanoparticles from root extract of Lepidium draba weed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Synthesized NPs using plant extracts are more advantageous than intracellular synthesis using microorganisms since it does not need complex and specialized processes such as isolation, culture maintenance and multiple purification steps. Due to the above, it has become a major focus leading researchers to develop green methods using different parts of the plant, e.g., from leaf 17 19 , peel 20 flower 21 , fruit 22 and root 23 . Many compounds present in the plant extract (e.g., p1olyphenols, ascorbic acids, flavonoids, terpenoids and proteins) play an essential role in the mechanism of metal ions uptake, reduction of precursor salt as well as capping agents and some of them with inherent antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesized NPs using plant extracts are more advantageous than intracellular synthesis using microorganisms since it does not need complex and specialized processes such as isolation, culture maintenance and multiple purification steps. Due to the above, it has become a major focus leading researchers to develop green methods using different parts of the plant, e.g., from leaf 17 19 , peel 20 flower 21 , fruit 22 and root 23 . Many compounds present in the plant extract (e.g., p1olyphenols, ascorbic acids, flavonoids, terpenoids and proteins) play an essential role in the mechanism of metal ions uptake, reduction of precursor salt as well as capping agents and some of them with inherent antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…The silver nanoparticles synthesized with AgNO 3 and leaf extract of Annona reticulata showed potent activity against Bacillus cereus and Staphylococcus aureus at 125 and 31.25 μg/mL; while it inhibits Escherichia coli , Pseudomonas aeruginosa and Candida albicans at 62.5 μg/mL . Similarly, the s ilver nanoparticles prepared with increased concentrations of Lepidium draba root extract showed that the nanoparticle with reduced size posses strong activity against S. aureus , B. cereus , E. coli, and S. Typhimurium . Again the silver nanoparticles from Caesalpinia coriaria leaf extract are active against antibiotic‐resistant S. aureus , E. coli , Klebsiella pneumoniae , and P. aeruginosa ; while silver nanoparticles of Helicteres isora root extract possess antibacterial with antioxidant activity; similar to our observation with silver nanoparticles of A. lebbeck bark extract but at extremely low concentrations.…”
Section: Discusssionmentioning
confidence: 98%
“…The image also showed the damaged cell wall (pores) and cell membrane leading to the leakage of cytosolic content to lysis, compared to the untreated bacteria with normal rod‐shaped morphology, due to the differences in their sensitivity pattern (MIC 0.50 and 0.60 μM), along with variations in inoculum size, resistance level, peptidoglycan, biochemical and molecular structure as well as other components. Further, nanoparticles not only act on bacteria by direct contact, but also penetrate rapidly to interact with microbial DNA, that prevents the bacterial to develop resistance, and thus nanoparticles are less disposed to bacterial resistance . This suggests that Ag‐NP‐AE can be helpful in the management of those MDR‐bacterial infections.…”
Section: Discusssionmentioning
confidence: 99%
“…The medical properties of gum are the use of it as a carminative, mild diuretic, diaphoretic, expectorant, stimulant, vasodilator, and antimicrobial agent. It is listed in the British pharmacopoeia as an expectorant and antispasmodic drug; occasionally, it is also used for chronic bronchitis and persistent coughs [42].…”
Section: Introductionmentioning
confidence: 99%